(untitled) (Journal of Naval Architecture and Marine Engineering, 2023)
The finite element method (FEM) is already well-established as a strong and widely used numerical analytical methodology for determining solutions to a wide variety of structural mechanics issues. One of the most significant subjects in the design of not only ships, but also airplanes and other structures is the configuration of plate type structures, particularly with discontinuities. A structural discontinuity occurs when the cross section of a structural part changes abruptly due to material defects or high stress locations. This article primarily focuses on the fundamental concepts of FEM for finding solutions of two-dimensional plane stress and plane strain problems to evaluate stresses such as normal stress, shear stress, and von-mises stress at the four integration points (gauss points) for various sections of ship structures (especially at the most vulnerable areas), such as plate with holes, plate with bracket and holes, and plate with fillets. To study structural discontinuity problems for various ship structures, an object-oriented programming method is used to create a finite element program for four node quadrilateral elements. With the aid of commercial finite element analysis software, the analysis findings of gauss point stresses for different ship sections produced from the developed program are validated.